SLIP OF THE TONGUE SPEECH PRODUCTION OF ENGLISH AND LITERATURE STUDENTS IN PRESENTATION (CASE STUDY IN PROPOSAL SEMINAR EXAMINATION) - Nur, Serliah; Asnur , Sardian Maharani; Alessandro, Zulfadio Akbar Bintang (Elite : English and Literature Journal, 2025)
This study aimed to examine the various types of slips of the tongue produced by students of the English and Literature Department at the State Islamic University of Alauddin Makassar during seminar proposal presentations. It also sought to explore the underlying factors contributing to the occurrence of these speech errors. Using a qualitative descriptive approach, data were collected from five participants through audio recordings and follow-up interviews. The findings revealed six types of slips of the tongue based on Fromkin’s (1973) classification: anticipation, exchange, addition, perseveration, substitution, and deletion, with addition being the most frequent. Interview results indicated that cognitive load was the main contributing factor, categorized into intrinsic, extraneous, and germane cognitive load. These findings suggest that slips of the tongue are closely linked to the cognitive demands students face during formal academic speaking tasks.